The Influence Of Competence And Work Environment On The Performance Of Karawang District Inspectorate Employees - Sopia Marwah Hajariani; Budi Rismayadi; Wike Pertiwi (International Journal of Management, Economic, Business and Accounting, 2024)
Purpose of the study — This study aims to determine and analyze the partial and simultaneous effects of competence and work environment on employee performance. Research method—A quantitative approach with correlational research method is used in this study. The employees of the Inspectorate Office of Karawang Regency are the subjects of this research. Saturated sampling technique is used to collect data through questionnaire distribution and observation. Result— The results show that there is a positive and significant influence between competence and employee performance. Similarly, employee performance is positively and significantly influenced by the work environment. Additionally, there is a significant and positive simultaneous influence between employee performance, competence, and work environment. Conclusion— This study provides insights into the importance of competence and work environment in enhancing employee performance. The findings suggest that organizations should focus on improving employee competence and creating a conducive work environment to enhance overall employee performance.